The longest trip home : a memoir - Grogan, John, 1957- (New York, NY : William Morrow, 2008)
John Grogan tells the story of a son in the making, a universal journey of love, faith, and family that explores what it means to break away and find the way home once again.
Keywords: Grogan, John, -- 1957-; Journalists -- United States -- Biography